Proposed Improvement on Supply Chain System to Minimize The Bullwhip Effect Phenomenon with Monte Carlo Simulation Approach - Dyah Lintang Trenggonowati; Maria Ulfah; Asep Ridwan; Rasie Arthafia (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2021)
PT XYZ is one of the most company which produce welded steel pipe in Indonesia such as longitudinal and spiral pipes. In order to meet consumer’s demand, this company faced with an obstacle namely the distortion of information in supply chain. Distortion of information from downstream to upstream channel causes the difference between the product demand from consumer to PT XYZ and order of raw materials from PT XYZ to the supplier which is called the bullwhip effect. The objective of this research is to calculate the value of bullwhip effect as well as designing improvements to minimize the bullwhip effect. Based on the research results, obtained the index value of bullwhip effect on longitudinal pipe products is 1.06 and the index value of bullwhip effect on spiral pipe products is 0.80. The improvement design to minimize the phenomenon of bullwhip effect is to build an integrated information system for the customer, manufacturer, and supplier. The method that is used to improve the index value of bullwhip effect is Monte Carlo simulation. Monte Carlo simulation is used to obtain the order number of raw materials in order to approach the number of consumer’s demand. After applying the Monte Carlo simulation, obtained the index value of bullwhip effect on longitudinal pipe product is 1.01 and the index value of bullwhip effect on spiral pipe products is 1.00. It can be concluded that the use of Monte Carlo simulation had been optimizing the index value of bullwhip effect amounted to 4.71% for longitudinal pipe products and 25% for spiral pipe products.